Ajuste da malha triangulada resultante das operações booleanas de um modelador de sólidos - Christiane de Lisieux Leal e Mol (2004)
This work presents a new method and algorithm to optimize the quality in finite element meshes. Its related to the GSM Gopac Solid Modeler used to define 3D computational geometry in electromagnetic problems. The GSM generates triangular superficial meshes over solid objects that will be employed by volumetric mesh generators. Usually, the Boolean Operations and Assembly Operations yields the badly formed elements, these may present small angle or area during the determination of the intersection points between two regions meshed. The method of Suavização Laplaciana has been proposed to minimize this problem. However, in order to improve the quality of the mesh, an algorithm to join its elements (point-point, edge-edge and edge-face) may be used to control the intersection point determination. The distance between the elements is smaller than the input tolerance defined by the modeler. The results show the reduction of the badly formed elements into the intersection regions, and the improvement of the mesh quality.